Effects of Fe diffusion driven by thermal history on the tribological behaviour of Al–Si coated 22MnB5 under varying load conditions in hot stamping - Min-Ki Ji; Hyunsung Son; Gyu Hyeon Shim; Ho Seon Ahn; Tea-Sung Jun (Journal of Materials Research and Technology)
With the advancement of the automotive industry, the demand for superior mechanical properties has inevitably driven changes in steel sheet thickness. Consequently, considerable attention has been given to variations in thermal history that arise due to differences in thickness, even under identical heat treatment conditions. This study examined the influence of thermal history on hot stamping wear behaviour by varying only the thickness of the base material, 22MnB5 boron steel, to 1.2 mm and 1.4 mm under identical processing conditions. After heat treatment, Fe2O3, an Fe oxide, was detected only on the surface of the 1.2 mm steel sheet, leading to a distinct difference in tribological behaviour between the two materials. This disparity is attributed to variations in Fe diffusion during heat treatment, governed by thermal history. These findings offer valuable insights into the role of thermal history in diffusion and phase transformation during heat treatment, contributing to a deeper understanding of material behaviour in hot stamping applications.